Structural synthesis of five-degree-of-freedom hybrid kinematics mechanism. Issue 4 (27th May 2016) - Zhou, Hui; Qin, Youlei; Chen, Hai; Ge, Shuyi; Cao, Yi
ABSTRACT: The structural synthesis of mechanisms is the prerequisite of mechanical design, thereby, it is necessary to formulate special care to be taken to the structural synthesis of mechanisms, especially for the type synthesis of hybrid kinematics mechanism (HKM). This paper presents a very simple and effective method of structural synthesis for HKM based on set theory. The basic concept and mathematical operation of G F set are first introduced. Based on a G F set, the principle of type synthesis for serial mechanisms, parallel mechanisms and HKM is presented, especially, a detailed algorithm of type synthesis for HKM is proposed as well. It is shown that type synthesis of HKM can be developed by the combination of elements of G F set and rotation axis movement theorem. In order to demonstrate the applicability of the type synthesis principle, the structural synthesis of five-degree-of-freedom HKM is given in detail. A further investigation shows that the structure of three-translational and two-rotational HKM only have one type, whereas, two-translational and three-rotational HKM can be categorised into two types, i.e. and .